Spinal cord injury providers' perspectives on managing sublesional osteoporosis. (3rd July 2020) - Weaver, Frances M.; Etingen, Bella; Guihan, Marylou; Ray, Cara; Priebe, Michael; Burns, Stephen; Carbone, Laura
Abstract : Objective: Persons with spinal cord injuries (SCI) experience rapid sublesional bone loss following injury (1, 3). Evidence on preventing/managing osteoporosis in SCI is lacking. This project examined how providers manage bone loss in SCI. Design: Telephone interviews with SCI providers. Setting: VA SCI centers and clinics. Participants: Veterans Administration SCI centers and clinics were categorized on their average number of dual-energy X-ray absorptiometry (DXA) scans (FY2014-2016). Twelve SCI providers from high and low DXA-ordering sites were interviewed. Questions included osteoporosis screening/diagnosis, prevention/treatment strategies, secondary causes of osteoporosis, and osteoporotic fracture complications. Interviews were audio-recorded, transcribed, and analyzed. Results: Providers described a lack of standardized guidelines for managing osteoporosis in SCI. They most often screened for osteoporosis using DXA when: (1) considering use of a new device or activity, (2) for patients with a history of fracture. Some providers assumed that non-ambulatory SCI patients already have osteoporosis so infrequently ordered DXAs. Assessment of secondary causes of osteoporosis was uncommon. Fracture prevention strategies identified included weight-bearing and engaging in activities like adaptive sports. Vitamin D and calcium were frequently prescribed as a result of deficiencies identified during lab testing. Providers seldom prescribed FDA-approved medications for osteoporosis. Post-fracture complications encountered included nonunion/malunion and compartment syndrome. Providers indicated that patients often experienced psychological stress, anxiety and depression following fractures. Conclusion: Providers described a lack of evidence for screening and management of patients with SCI and osteoporosis. Future efforts should include developing evidence-informed guidelines to aid providers in osteoporosis management.